Basic Study on Deformation Evaluation of Steel Wire Mesh for Rational Gabion Structure Design - Hiroshi Nakazawa; Tsuyoshi Nishi; Hiroyuki Kurihara; Daisuke Suetsugu; Tadashi Hara (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2019)
Gabion structures are used in a variety of ways in Japan and around the world because they allow for the creation of simple structures at highly reasonable construction costs and completion periods. Previous earthquake damage surveys have shown that, in many cases, gabion structures did not collapse even though deformation was allowed, and have demonstrated that the wire mesh used in their construction has a high confinement effect on the stones filling the gabion. Despite this, gabions have not been actively utilized, nor have they been used to construct permanent structures in Japan because the design and construction of such structures are based on experience, and a standardized design method has not been developed. Hence, in order to facilitate development a design method for gabion-based structures, we must first go back to the basics and establish a detailed explanation of the wire mesh deformation mechanism of such structures. In this study, we performed tensile tests on wire meshes of different shapes in order to determine their strength and deformation characteristics and then conducted numerical analyses using the results obtained. The tensile tests revealed that deformation characteristics differed depending on the mesh shape and tensile direction. We also showed that the direction in which the tension acts and the mesh nodes are important, and that the test results could be reproduced via numerical analysis with the finite element method by using beam elements.